2014
DOI: 10.14712/23362936.2014.3
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Inflammation-related Genes after Intense Exercise

Abstract: Abstract:The present study focused on the identification of the difference in expression of inflammation-related genes after intense exercise by oligonucleotide microarray methods. This may finally lead to an improved understanding of underlying cellular and molecular mechanism of the immunological alterations in response to exercises. The study group consisted of three healthy road cyclists. Peripheral blood mononuclear cells (PBMCs) were collected preexercise, immediately post-exercise and after 15 min of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
(20 reference statements)
1
11
0
1
Order By: Relevance
“… 69 ↑ after MT (of which 64 were identical to RTE) Pathways regulated were related to inflammation, stress response, signal transduction, and apoptosis. Kimsa et al [ 44 ] Ergometric cycling and expression pattern of inflammation-related genes. Blood samples were drawn before exercise (pre-ex), immediately after exercise (post-ex), and 15 min into recovery.…”
Section: Acute Exercise and Gene Expression Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“… 69 ↑ after MT (of which 64 were identical to RTE) Pathways regulated were related to inflammation, stress response, signal transduction, and apoptosis. Kimsa et al [ 44 ] Ergometric cycling and expression pattern of inflammation-related genes. Blood samples were drawn before exercise (pre-ex), immediately after exercise (post-ex), and 15 min into recovery.…”
Section: Acute Exercise and Gene Expression Studiesmentioning
confidence: 99%
“…When using this approach, Kimsa et al found that an acute bout of bicycling regulated several biological pathways such as cytokine-mediated signaling pathways (IL6, IL8, and IL1B), intracellular signaling (IL5RA, IL6, and IL8), cell communication and cell-to-cell signaling (interleukin 2 receptor beta (IL2RB), colony-stimulating factor 2 (CSF2), and interleukin 1 receptor-like 1 (IL1R1). In total, ten inflammation-related genes were changed after exercise [ 44 ].…”
Section: Gene Expression Studies In Pbmcs—endurance Trainingmentioning
confidence: 99%
“…Changes in genes associated with inflammation and HSP show the result of alterations in signalling via these pathways. There is considerable evidence demonstrating the influence of various exercise types on inflammation [ 13 , 14 ] and gene expression of heat shock proteins [ 15 , 16 ], thereby mediating the health benefits of episodic and prolonged exercise.…”
Section: Introductionmentioning
confidence: 99%
“…The health-promoting effects of exercise are associated with interleukin production, eliciting the anti-inflammatory response by decreasing inflammation [ 10 ] and increasing stress tolerance. Therefore, determining the balance of pro- and anti-inflammatory cytokines after exercise is important, not only in sports, but also in terms of health [ 13 ]. Additionally, the type of training is one of many factors that can influence the adaptive effect to exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Em humanos, durante e após as sessões de exercício físico, alguns leucócitos como linfócitos, macrófagos e células natural killer (NK) apresentam alterações funcionais e metabólicas comprometendo as respostas imunológica e inflamatória (GLEESON, 2007;KIMSA et al, 2014;MORO-GARCIA et al, 2014), principalmente nos exercícios físicos realizados de modo intenso e extenuante (MALM, 2006). Na competição de maratona, as alterações mais evidentes ocorrem nas células NK, macrófagos e neutrófilos (MOOREN et al, 2012;NIEMAN, 1997).…”
Section: Função Imune E Exercício Físicounclassified